Drastic Allure: Timbre Between the Sublime and the Grain. Issue 6 (2nd November 2017) - van Elferen, Isabella
Abstract : This article analyses the binarism that pervades critical assessments of tone colour. In musicology, sound studies, and aesthetics alike, timbre is either considered in a materialist way as the manipulation of sound waves and instruments, or, in idealist fashion, as a sublime and unapproachable Thing that defies description. Exploring the timbral sublime and its friction with timbral materiality, I argue that a theorisation of tone colour must start with the acknowledgement of the timbral paradox: timbre undeniably has material as well as immaterial components. Timbre's paradoxical im/materiality engenders a sublime aesthetic experience that can be described as the aporia of being drawn into a void which appears to be real but which—the closer you get to it—flickers in and out of earshot and comprehension. The paradox of tone colour, thus, is precisely its allure.